1999
DOI: 10.1002/(sici)1097-4628(19991205)74:10<2378::aid-app5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Poly(styrene-co-N-butylmaleimide) macroinitiators by controlled autopolymerization and related block copolymers

Abstract: Autopolymerization of styrene-N-butylmaleimide mixtures at 125 or 140°C in the presence of a stable nitroxyl radical [2,2,6,6-tetramethylpiperidin-1-yloxyl (TEMPO)] was found to proceed in a pseudoliving manner. Unimolecular initiators, which were originated by trapping self-generated radical species with TEMPO, took part in the process. Under the studied experimental conditions, the TEMPO-controlled autopolymerization with a varying comonomer ratio provided virtually alternating copolymers of narrow molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(17 reference statements)
1
12
0
Order By: Relevance
“…Copolymerizations of N-alkyl-or N-phenylmaleimides with St in bulk or solution by 'controlled' / living radical polymerization methods like ATRP [20,21] or SFRP [22][23][24][25][26] revealed that alternating copolymers or block copolymers with controlled molecular weight and low polydispersities can be prepared.…”
Section: Copolymerization Of Maleimide Monomer Cobami With Stsupporting
confidence: 85%
“…Copolymerizations of N-alkyl-or N-phenylmaleimides with St in bulk or solution by 'controlled' / living radical polymerization methods like ATRP [20,21] or SFRP [22][23][24][25][26] revealed that alternating copolymers or block copolymers with controlled molecular weight and low polydispersities can be prepared.…”
Section: Copolymerization Of Maleimide Monomer Cobami With Stsupporting
confidence: 85%
“…For instance, the first example of nitroxide mediated alternating copolymerization of styrene and N-butyl maleimide was published by Lokaj and co-workers in 1999. [65] Shortly after, the same group described the NMP of styrene and MAh. [66] In these two examples, TEMPO was used as control agent (i.e., first generation nitroxide) and therefore the molecular weight distributions of the formed alternating copolymers were relatively broad.…”
Section: Controlled Radical Copolymerization Of Styrene and Strong Elmentioning
confidence: 99%
“…Schmidt-Naake et al [55] reported the copolymerization of styrene and various N-substituted maleimides, that is, N-cyclohexyl maleimide [54,55], N-butyl maleimide, and N-phenyl maleimide in the presence of the stable free radical 2,2,6,6-tetramethylpiperidin-1-yloxyl (TEMPO) initiated by benzoyl peroxide, while Lokaj et al studied the copolymerization of styrene with maleimide [56], N-butyl maleimide [57], or N-phenyl maleimide [58] in the presence of TEMPO and initiated by autopolymerization (i.e., styrene thermal initiation). As in the case of conventional radical polymerization, an alternating copolymer was observed, but the polymerization technique employed allowed better control over the molecular weight and molecular weight distribution.…”
Section: Controlled Radical Polymerizationmentioning
confidence: 99%